Overview and Management of Chronic Kidney Disease Inpatients at Royal Prima General Hospital Medan in 2020 - Yuke Armika; Nerseri Barus; Sri Lestari Ramadhani Nasution (HM Publisher, 2022)
Chronic kidney disease (CKD) is a condition in which there is a gradual decline in kidney function. This disease is progressive and usually irreversible. Indications for hospitalized CKD patients with severe complications and do not allow inpatient therapy. This study was aimed to describe the overview and management of chronic kidney disease inpatient in Royal Prima General Hospital Medan. The type of research used is research with a descriptive and retrospective case study design. This study is based on medical record data related to inpatient CKD patients' diagnostic and management features at the Royal Prima General Hospital Medan in 2020. The research subjects were all inpatients diagnosed with CKD, whereas 100 research subjects with complete medical records were included in this study. It was found that the highest age group was 57-65 years, as much as 37.0%, and men as much as 27%. The chief complaint was shortness of breath at 43% and additional complaints, the most of which were fever + low back pain + edema at 38%. On physical examination, most of the inspections were weak, 55%. Most palpation was sociable 57%. There was auscultation of four abdominal regions and normal positive bowel sounds (93%). Complete blood count + blood sugar level + electrolytes + urea + creatinine 70%, the most combination medication is NaCl 0.9% + Furosemide injection 31%. Based on the length of stay, the longest was 13-14 days (20%).